Functional Movement Screen Relationship With Futsal Athletes' Anxiety On Kendal Porprov Team - Nico Armando; Ranu Baskora Aji Putra (Universitas Negeri Semarang, 2026)
This study was motivated by the importance of the relationship between physical and psychological conditions in futsal athletes, particularly movement quality measured through the Functional Movement Screen (FMS) and athletes' anxiety levels. This study aimed to determine the relationship between FMS scores and anxiety levels among futsal athletes on the Kendal Regency Porprov (Provincial Multi-Sport Games) Team. A quantitative approach with a cross-sectional correlational survey design was employed. The sample consisted of 35 futsal athletes selected using purposive sampling. Movement quality data were collected using the FMS test, while anxiety levels were measured using the Sport Competition Anxiety Test (SCAT). Data were analyzed using the Spearman Rank correlation test following a normality test. Results showed a mean FMS score of 18.29 (very good category) and a mean anxiety score of 19.69 (moderate category). The Spearman correlation test yielded a coefficient of 0.155 with a significance value of 0.372 (p>0.05), indicating no significant relationship between FMS and anxiety levels. It is concluded that movement quality, as measured by FMS, is not significantly associated with anxiety levels among futsal athletes on the Kendal Regency Porprov Team. Further research with larger samples and additional psychological variables is recommended to better understand this relationship.